A modern Nordic saga : politics, economy and society - Czarny, Ryszard Michał (Springer, 2017)
This book focuses on the Nordic countries through a European perspective and wishes to draw attention to their place in the new world order. The volume emphasizes the specificity of their cooperation within the region itself as well as within the European Union, and stresses the importance of the Nordic region as an area of possibilities and tangible chances resulting from the challenges of globalization. The social, cultural, political and economic dimensions of these countries are characterized by cooperation among states, their collaboration with other regional organizations and within international projects, as well as exchange of viewpoints on the specificity of the current Norden issues. The cooperation of the Nordic countries and their inhabitants as well as migrations between the Scandinavian states have been a trademark of the common and shared history of Norden.- Resumé vydavatel
Keywords: udržitelný rozvoj; regionální geografie; sustainable development; regional geography; Skandinávie -- dějiny; Skandinávie -- politika a vláda; Skandinávie -- hospodářské poměry; Skandinávie -- společenské poměry; Scandinavia -- history; Scandinavia -- politics and government; Scandinavia -- economic conditions; Scandinavia -- social conditions; elektronické knihy; kolektivní monografie; electronic books; collective monographs